The effect of recovery satisfaction on citizens loyalty perception: a case study of mobile government services - Ibrahim Almarashdeh (Institute of Advanced Engineering and Science, 2020)
Use of mobile services is an integral part of today’s life. Organizations, government agencies as well as service providers in the market employ mobile services or application in reaching their citizens or users worldwide. Notably, service failure issues might frustrate users in using mobile service, but usually, service providers would employ the strategy of recovery as solution. Recovery strategy aims to sustain the relationship with users following service failure. Somehow, the factors that might impact recovery process are unclear. It is also unclear if users will use the service again following the completion of recovery process. Hence, in this study, a survey on 743 adults was carried out, and the data were analyzed using SEM to determine the factors that impact users’ recovery satisfaction the most and the impact of recovery satisfaction on citizens loyalty to use mobile government in the future. The finding of this study illustrated that expect of self-efficacy, all factors proposed in the research model found to has a significant impact on recovery satisfaction. Among all the supported hypothesis, the highest impact on recovery satisfaction comes from perceived trust in government as the initial predictor to use the service